Umbilical Venous Catheter Position Evaluation in Hasan Sadikin General Hospital : Overview of the Time Required - Suryaningrat, Filla Reviyani; Primadi, Aris; Kadi, Fiva Aprilia; Hudayari, Devatri; Ediwan, Natasha Amalda; Yuniati, Tetty (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2024)
Background: An umbilical venous catheter (UVC) is one of the most frequently used access in neonates. In developed countries, bedside ultrasonography (USG) is used in assessing the position of the UVC catheter’s tip. However, this is difficult to be implemented in developing countries. In Indonesia, which categorized as a middle- income developing country, the evaluation of UVC mainly used chest radiographs. However, this procedure would take time. The delay in ascertaining UVC positioning through chest radiography among neonatologists in Indonesia remains unstudied, despite its potential on the clinical efficacy. Therefore, this study aimed to determine the time required for the installation of the UVC and the interval from the completion of UVC insertion until the release of the chest radiography result. Method: In this prospective observational cohort study, neonates requiring UVC access were examined in Dr. Hasan Sadikin Hospital in Bandung, West Java. Patients underwent anthropometric measurements and UVC installation. Duration required for UVC installation and the interval between the completion of UVC insertion and the release of the chest radiography result were documented. Descriptive data were shown in percentage, mean and standard deviation. Result: 127 neonates were studied. The average time taken for UVC insertion was 31 minutes and the average time taken from the completion of UVC insertion until the release of chest radiography results was 6 hours. Conclusion: The long wait for chest radiography results significantly delayed the administration of fluids, medications, and parenteral nutrition in this study. Therefore, we need alternative tools to evaluate the UVC location that can be used bedside right after the installation.